Prevalence and Associated Factors of Stress and Depression in COVID-19 Patients Who have been Treated Hospitalized and Treated at Home in Na Noi District, Nan Province - Mongkolkum, Witsanu; sukolsate, Apaiporn (Journal of Preventive Medicine Association of Thailand, 2023)
COVID-19 infection, in addition to causing physical illness, it also has an impact on mental health, especially stress and depression, which is why it is necessary to screen for stress and depression along with the treatment of physical diseases as well. During the COVID-19 pandemic In Nan Province, Na Noi Hospital has arranged its services by classifying patients into 4 groups: those who are admitted to Cohort ward; those who are admitted to Field hospital, those who are closely monitor at home (Home-isolation) and those who are selfcare under supervise by healthcare provider (self-isolation) Objective: To determine the prevalence of stress and depression caused by patients infected with COVID-19. They were admitted to the four groups of Na Noi Hospital and to identify factors that associated with stress and depression. Method: This study is a cross-sectional-analytic study. Collected data from interview records with COVID-19 patients, by telephone, who treated in Na Noi Hospital’s service system between August 2021 to May 2022.General information including gender, age, education level, etc., average monthly income, underlying medical conditions, history of Covid-19 vaccination and number of times. Assess stress with Stress Assessment score (ST-5), screening risk of depression with 2-question depression risk screening (2Q), and assess severity of depression with 9-question depressive severity assessment (9Q). Non-parametric statistics analysis with a computer program, general data were analyzed with descriptive statistics, namely frequency, percentage, comparing factors affecting stress and depression with Chi-square statistics. Analyzed severity of Stress (ST-5 score) and severity of depression symptoms (9Q score), with Mann Whintney U test statistics if compare mean rank between two independent sample groups and with Kruskal Wallis test statistics if compare between more than two sample groups. Results: The prevalence of depression in COVID-19 patients was 9.9%, with female patients experiencing a statistically significantly higher risk than males at p-value=0.004. The severity of depression is highest in patients with an associate/diploma level and higher than patients with a high school/vocational education, statistically significant at p-value=0.01. Patients with a bachelor’s degree have a higher severity of depression than patients with a high school/vocational education, statistically significant at p-value=0.02. Patients who treated in the Cohort ward have a highest severity of depression and higher than patients who treated at home, statistically significant at p-value=0.001 for Home-Isolation and p-value=0.002 for Self-Isolation. The prevalence of moderate stress in Covid-19 patients was 16.98%, the severe stress was 1.41%, and the most severe stress was 1.89%, respectively. Gender, education, income level, history of comorbidities, history of COVID-19 vaccination, as well as all 4 forms of treatment did not affect the patient’s stress level. Conclusion: The COVID-19 pandemic will continue to be a national public health issue. The findings in this study suggest that the mental health of COVID-19 patients should be assessed and treated alongside all physical treatments, especially those at high risk, female patients, and those admitted as hospital patients. In addition, it is best to consider treating patients at home even if they have symptoms or risk factors for comorbidities, because it has been found that home treatment has a lower prevalence of depression and stress. They must be closely monitored and have a referral system in place if symptoms worsen.